Mathematical model of sorption process of liquid organic substances by polymeric membrane elements - Буртная, Инесса Анатольевна; Ружинська, Людмила Іванівна; Мурашко, Михайло Михайлович; Руденко, Леся Сергіївна (Eastern-European Journal of Enterprise Technologies, 2014)
The results of the study of pharmaceutical wastewater treatment from organic impurities through sorption and desorption of organic solvents by polymeric membrane elements are presented in the paper. The processes of sorption by membrane elements are characterized by high efficiency, energy saving, possibility of fine separation of mixtures with obtaining high-quality products and their undeniable environmental safety. Sorption process lies in passing of certain organic compounds (solvents) of wastewater to the body of nonporous polymeric membrane elements (adsorbent), with the possibility of further desorption of absorbed compounds. Using such membrane technology allows to achieve a significant impurity concentration reduction, high wastewater treatment efficiency and raw materials consumption coefficient reduction due to the return of organic solvents in the production process. Membrane sorption with the subsequent desorption is a multifactorial process that is associated with the dissolution of organic components in polymeric membranes, which is accompanied by swelling of the membrane materials in organic solvents. The results of experimental studies of the dissolution kinetics of polar and nonpolar molecules in nonpolar membranes, swelling processes of polymeric membrane materials in organic solvents, diffusion coefficients of the most common solvents in polymeric membranes are given in the paper. Based on the experiments, the mathematical model of the adsorption process of organic solvents by polymeric membrane elements was developed. Mathematical model adequately describes the concentration distribution over the polymeric membrane element thickness. The model takes into account all process peculiarities, including swelling. Based on the model, concentrations of the most common organic solvents in industry were calculated in different sections of membrane elements. The results of experimental and theoretical research can be used in designing plants for water treatment from organic solvents, particularly, in selecting the fixed-bed adsorber design in the form of membrane attachment.